Religious Rights and State Presence in John Locke's Liberalism Perspective (Reflections on the 1984 Tanjung Priok Case) - Salsabila, Orchida Nadia; Ghofur, Nilman; Mujib, M. Misbahul (UIN Sunan Kalijaga Yogyakarta, 2023)
Upholding human rights as a part of international law without the presence of the state would seem impossible because the state is an essential element of international law. What is interesting is what happened in the 1984 Tanjung Priok Indonesia case, where human rights violations occurred because of the state's presence. The question is, how should the state's presence be? This study reflected on the 1984 Tanjung Priok case as a lesson on how countries should be involved in religious rights so as not to injure human rights. Answering that question, this study used a normative approach and John Locke's theory of liberalism. Furthermore, this study found that during the New Order era, the state's presence in civil rights was too deep, especially those related to religious rights. The presence of the state is indeed important, but the presence of the state, which is very dominant for reasons of political stability by depriving people of the right to practice their religion, cannot be justified. In addition, it is also unacceptable if the state reduces civil rights because of religious considerations. Although it is difficult, if the state has a certain ideology or religion, the state should not harm individual rights, including the rights of other religions and the religious rights of its citizens that are different. The state must not interfere too deeply or get too involved in its own ideology/religion, which then prohibits the religious rights of adherents of other religions who are its citizens.